Differential Response Of Early And Intermediate Flowering Strawberry Cultivars To Nursery Late-Season Nitrogen Applications And Digging Date - Kirschbaum, Daniel Santiago; Larson, Kirk D.; Weinbaum, Steven A.; DeJong, Theodore M. (2018)
The response of ‘Ventana’, an early flowering cultivar, and ‘Camarosa’, an intermediate flowering cultivar, to nursery late-season nitrogen (N) applications and digging date were studied in strawberry (Fragaria x ananassa Duch). Two experiments were conducted. In the first experiment, runner plants dug on September 20 and October 11 from a high-latitude nursery in California, were established in growth chambers set at 25°/15ºC day/night temperature, 12-h photoperiod, and grown for 90 days. Compared to the first experiment, in the second experiment plants received extra N (foliar-applied) in the nursery in late summer, and runner plants were not grown in GC but in open field (Irvine, California). In the second experiment, runner plants were dug on Sept 20 and Oct 2. In both experiments, plants dug in September were exposed to ~100 chilling units (CU: hours ≤7.2°C) and plants dug in October were exposed to ~300 CU. As a result, October-dug plants had greater crown and root dry weight, and greater concentration of starch and total nonstructural carbohydrates (TNC) in leaves, crowns and roots, compared to September-dug plants. In control plants, from September to October, root TNC concentration increased in ‘Camarosa’ from ~6% to ~11%, and in ‘Ventana’ from ~14% to ~21%, and leaf N concentration ranged from 1.47 to 1.81% in ‘Camarosa’, and from 1.60 to 1.96% in ‘Ventana’. Late summer N applications increased plant N concentration and early-season yields. Late-summer nursery N applications reduced dead leaf biomass (DLB) and dead leaf area (DLA) in both cultivars, although ‘Ventana’ had lower DLB and DLA than ‘Camarosa’. ‘Ventana’ had a greater leaf number and flowered earlier, and had greater early fruit production than ‘Camarosa’. The genetic earliness of ‘Ventana’ would be correlated with the potential of the plant for accumulation of higher initial levels of leaf N and root TNC, and for having greater leaf longevity, compared to ‘Camarosa’.